2021
DOI: 10.1093/plphys/kiab051
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional electron transfer between H2 and NADPH mitigates light fluctuation responses in green algae

Abstract: The metabolism of green algae has been the focus of much research over the last century. These photosynthetic organisms can thrive under various conditions and adapt quickly to changing environments by concomitant usage of several metabolic apparatuses. The main electron coordinator in their chloroplasts, nicotinamide adenine dinucleotide phosphate (NADPH), participates in many enzymatic activities and is also responsible for inter-organellar communication. Under anaerobic conditions, green algae also accumula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
3
8
0
Order By: Relevance
“…5b). The results show that the rate of H2 accumulation is impaired in all light fluctuations, following a short burst of H2 evolution at light onset, as was previously described (Milrad et al, 2021). In addition, we observed no significant changes in-between fluctuations.…”
Section: Dark Recovery Of the Initial Electron Transfer Ratesupporting
confidence: 88%
See 2 more Smart Citations
“…5b). The results show that the rate of H2 accumulation is impaired in all light fluctuations, following a short burst of H2 evolution at light onset, as was previously described (Milrad et al, 2021). In addition, we observed no significant changes in-between fluctuations.…”
Section: Dark Recovery Of the Initial Electron Transfer Ratesupporting
confidence: 88%
“…2d). It was previously shown that under anoxia, at light onset, NADPH levels decline due to its oxidation via Type-II NADPH dehydrogenase (Nda2) and/or shuttling via the Malate dehydrogenase (MDH) (Milrad et al, 2021). Our results here show that the rapid decline of NADPH concentration reaches steady state much faster in the initial exposure, approximately 10 seconds in the initial light exposure versus a minute in the successive fluctuations.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, NDA2‐mediated CET affects the NADPH/ATP ratio but is less effective in generating pmf than the cyanobacterial NDH‐1 complex. The non‐photochemical PQ‐reduction via NDA2 is the point of entry for electrons that derive from glycolysis and other breakdown processes to PETC, and can subsequently feed alternative electron sinks such as hydrogenases (Mignolet et al, 2012; Milrad et al, 2021) or PTOX (Saroussi et al, 2016).…”
Section: Nadh Dehydrogenase‐like Complexesmentioning
confidence: 99%
“…These data thus indicate another unknown terminal acceptor for H 2 oxidation. Recently,Milrad et al (2021) presented evidence that H 2 uptake in the darkness is accompanied by restoration of the NADPH pool. The latter suggests that H 2 may serve as an electron donor to NADP + via [FeFe]-hydrogenase.…”
mentioning
confidence: 99%